The Effects of Policy Change on Brazil's Public Higher Education System - Brasil, Felipe Goncalves [UNESP]; Mattos e Silva, Ivan Henrique de; Zambello, Aline Vanessa (Wiley-Blackwell, 2017)
This descriptive article presents a case study of the effects of policy change on the public higher-education system in Brazil, highlighting the significant differences in the system after President Lula's election in the mid-2000s. The data collected show changes to higher-education policy in the number of institutions, the number of spots offered, racial-quota policies, access, and the offer of public services through the adoption of electronic-government tools. The article also considers how these changes to the Brazilian system fit into studies carried out with two public-policy analysis models, multiple streams, and punctuated equilibrium.
Keywords: higher education; Brazil; multiple streams; punctuated equilibrium